2010
DOI: 10.1038/leu.2009.273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-risk cytogenetics and prior therapy on outcomes in patients with advanced relapsed or refractory multiple myeloma treated with lenalidomide plus dexaméthasone

Abstract: This retrospective analysis investigated the prognostic value of del(13) and t(4;14) abnormalities and the impact of prior treatment on outcomes in 207 heavily pretreated patients with relapsed or refractory multiple myeloma (MM) treated with lenalidomide plus dexamethasone. Patients with relapsed or refractory MM who had either earlier received thalidomide or bortezomib, or for whom continuation of these agents was contraindicated, and who had fluorescence in situ hybridization data available were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 18 publications
4
84
3
Order By: Relevance
“…However, we did not find a significant impact of bortezomib resistance. In the report by Avet-Loiseau et al 27 although earlier bortezomib use was associated with inferior PFS and OS in univariate, was not significant in multivariate analysis. The authors suggested that the OS of patients who had progressed on thalidomide was affected negatively, only if they also had received previous bortezomib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find a significant impact of bortezomib resistance. In the report by Avet-Loiseau et al 27 although earlier bortezomib use was associated with inferior PFS and OS in univariate, was not significant in multivariate analysis. The authors suggested that the OS of patients who had progressed on thalidomide was affected negatively, only if they also had received previous bortezomib.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our results in thalidomide-resistant patients are similar to that of thalidomideresistant patients treated in phase 2 or 3 trials. The median PFS of thalidomide refractory patients in MM009 and MM010 trials was 7 months (95% CI: 4.9-16.9), 26 the median PFS for thalidomide refractory patients in the report by Avet-Loiseau et al 27 was 5.7 months, whereas the median time to progression in immunomodulatory drug refractory patients in the MMY-3001 study was 6 months for patients treated with bortezomib and pegylated liposomal doxorubicin and 5.5 months for those treated with bortezomib alone. 28 It is also interesting that the addition of bortezomib to RD could not overcome the major detrimental effect of previous thalidomide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other studies of the impact of upfront bortezomib treatment on the outcome of relapse treatment with lenalidomide plus dexamethasone showed less favorable results. [26][27][28] Bortezomib retreatment has been investigated in a recent prospective Italian trial, where 40% of patients achieved a response with a TTP of 8 months and there was a better outcome in patients who achieved a complete response (CR) following prior bortezomib (see below). 29 …”
mentioning
confidence: 99%
“…5,6 The presence of t(4;14) was also found to predict shorter survival in patients with advanced relapsed or refractory disease treated with lenalidomide and dexamethasone (9.4 versus 15.4 months; P=0.005). 7 The (4;14) translocation results in increased expression of the oncogenes fibroblast growth factor receptor 3 (FGFR3) and multiple myeloma set domain (MMSET). [8][9][10] The chromosomal abnormality del(17p) is frequently associated with mutations in the TP53 gene or alterations in the p53 pathway.…”
Section: Introductionmentioning
confidence: 99%